THE DETERMINANTS OF STRATEGIC RENEWAL AND ITS IMPLICATION ON DYNAMIC CAPABILITY (EMPIRICAL STUDY IN OUTOMOTIVE INDUSTRY) - Oscar Jayanagara (Faculty of Economics and Business Universitas Pelita Harapan, 2023)
This research aims to investigate about the effect of innovation, performance feedback and organizational learning on strategic renewal and their implication on dynamc capability in automotive industry. The methodology of this research was explanatory research with hypothesis testing for examining ten hypotheses. Populations were the automotive companies in Indonesia, most of the brands are Toyota, Daihatsu & Honda. with sample size were 282 companies. Data for this study were collected using questionnaires and SEM (Structural Equation Modeling) was employed for data analysis techniques. The results of this research were as follows: innovation positively and significantly influenced strategic renewal; performance feedback positively and significantly influenced strategic renewal; organizational learning positively and significantly influenced strategic renewal; innovation positively and significantly influenced Dynamic capability; performance feedback positively and significantly influenced Dynamic capability; organizational learning positively and significantly influenced Dynamic capability; strategic renewal positively and significantly influenced Dynamic capability. The most significant is the influence of innovation to strategic renewal. All of seven hypotheses which proposed in this research were being given can be accepted. innovation as an independent variable was the strongest influence on strategic renewal, and strategic renewal was the strongest influence on dynamic capability. This study also provides discussion on the findings as well as limitations, theoretical and practical contribution, theoretical and managerial implications of the study, and suggestions for future research.